PENGARUH MODEL PEMBELAJARAN PROJECT BESED LEARNING (PjBL) TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN IPAS DIKELAS IV MIN 6 BANDAR LAMPUNG - Opi lia Ziareta; Subandi; Ayu Reza Ningrum (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Learning interest is one of the important factors influencing the success of the learning process, particularly in Natural and Social Sciences (IPAS) subjects that require students’ active involvement in understanding concepts contextually. The problem of teacher-centered learning approaches often results in low student participation and learning interest. This study aims to analyze the effect of implementing the Project Based Learning (PjBL) model on students’ learning interest in IPAS learning for fourth-grade students at MIN 6 Bandar Lampung. This research employed a quantitative approach using a quasi-experimental method involving an experimental class and a control class with a total of 64 students. Data were collected through observation, interviews, documentation, and learning interest questionnaires based on indicators of enjoyment, attention, interest, and student involvement. Data analysis was conducted through prerequisite tests, including normality and homogeneity tests, followed by hypothesis testing using the Independent Samples T-Test. The results showed that the implementation of the PjBL model had a significant effect on improving students’ learning interest. This finding was indicated by the difference in the average learning interest scores between the experimental class (71.31) and the control class (59.88), with a significance value of 0.000 (<0.05). Therefore, the Project Based Learning model is proven to be effective in enhancing students’ learning interest through contextual, collaborative, and product-oriented learning activities. ABSTRAK Minat belajar merupakan salah satu aspek penting dalam keberhasilan proses pembelajaran, terutama pada mata pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) yang membutuhkan keterlibatan aktif siswa dalam memahami konsep secara kontekstual. Permasalahan pembelajaran yang masih berorientasi pada guru menyebabkan rendahnya partisipasi dan ketertarikan siswa dalam proses belajar. Penelitian ini bertujuan untuk menganalisis pengaruh penerapan model Project Based Learning (PjBL) terhadap minat belajar siswa pada pembelajaran IPAS kelas IV di MIN 6 Bandar Lampung. Penelitian ini menggunakan pendekatan kuantitatif dengan metode quasi experiment melalui desain kelas eksperimen dan kelas kontrol yang melibatkan 64 siswa. Pengumpulan data dilakukan menggunakan observasi, wawancara, dokumentasi, dan angket minat belajar berdasarkan indikator perasaan senang, perhatian, ketertarikan, dan keterlibatan siswa. Data dianalisis melalui uji prasyarat berupa uji normalitas dan homogenitas serta pengujian hipotesis menggunakan Independent Samples T-Test. Hasil penelitian menunjukkan bahwa penerapan model PjBL memberikan pengaruh yang signifikan terhadap peningkatan minat belajar siswa. Hal tersebut ditunjukkan melalui perbedaan rata-rata skor minat belajar antara kelas eksperimen sebesar 71,31 dan kelas kontrol sebesar 59,88 dengan nilai signifikansi 0,000 (<0,05). Dengan demikian, model Project Based Learning terbukti efektif dalam meningkatkan minat belajar siswa melalui aktivitas pembelajaran yang berbasis proyek, kolaborasi, dan pengalaman belajar yang kontekstual.